Positive electrode active material and lithium secondary battery including the same

The bimodal positive electrode active material addresses coating imbalances by controlling cobalt concentration gradients, enhancing stability and energy density through uniform cobalt distribution, thus improving electrochemical performance.

JP7612642B2Active Publication Date: 2025-01-14ECOPRO BM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022171071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-26
Filing Date
2022-10-26
Publication Date
2025-01-14
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

Existing bimodal positive electrode active materials face issues with unbalanced coating distribution leading to instability and reduced electrochemical properties due to concentration gradients of cobalt in small and large particles, resulting in decreased energy density and stability.

Method used

A bimodal positive electrode active material is developed with a controlled cobalt concentration gradient that decreases from the surface to the center, ensuring uniform particle stability by adjusting the slope of this gradient for both small and large particles.

Benefits of technology

The solution enhances particle stability, increases energy density, and improves electrochemical performance by uniformly distributing cobalt concentration, thereby stabilizing the particles and maintaining structural integrity during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612642000001
    Figure 0007612642000001
  • Figure 0007612642000002
    Figure 0007612642000002
  • Figure 0007612642000003
    Figure 0007612642000003
Patent Text Reader

Abstract

To provide a positive electrode active material configured to improve the stability of particles by mitigating or preventing generation of cracks, a collapse of a crystal structure, and / or a change in crystal structure (phase transition) not only in the surface portions but also in the central portions of a first lithium composite oxide and a second lithium composite oxide.SOLUTION: A first lithium composite oxide and a second lithium composite oxide include at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide has a concentration gradient that decreases from a surface portion toward a central portion. When s1 represents an absolute value of a slope of the concentration gradient of the cobalt decreasing from the surface portion toward the central portion of the first lithium composite oxide and s2 represents an absolute value of a slope of the concentration gradient of the cobalt decreasing from the surface portion toward the central portion of the second lithium composite oxide, s1 and s2 may satisfy s1<s2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a bimodal type positive electrode active material including a first lithium composite oxide which is a small particle and a second lithium composite oxide which is a large particle, the positive electrode active material being capable of uniformly improving the particle stability of the small particles and the large particles by controlling the inclination of a concentration gradient in which cobalt decreases from the surface portion to the center portion in the small particles and the large particles, a positive electrode including the positive electrode active material, and a lithium secondary battery using the positive electrode. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries, and examples of such composite oxides that have been researched include LiCoO2, LiMn2O4, LiNiO2, and LiMnO2.

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and thus has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature properties. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems in rate characteristics.

[0007] Meanwhile, the lithium composite oxide contained in the positive electrode active material undergoes volume changes due to the intercalation / deintercalation of lithium ions into the lithium composite oxide during charging and discharging. Normally, lithium composite oxide is in the form of secondary particles formed by agglomeration of multiple primary particles, but if a sudden volume change occurs in the primary particles during charging and discharging, or if stress accumulates due to repeated charging and discharging, problems arise in that cracks occur in the secondary particles, or the crystal structure collapses or changes in the crystal structure (phase transition) occur.

[0008] These problems ultimately act as a cause of reduced stability and reliability of the positive electrode active material, and therefore various studies are being conducted to alleviate the volume change of the lithium composite oxide during charging and discharging, or to minimize the generation of stress due to the volume change, thereby preventing damage to the particles.

[0009] In addition, in recent years, bimodal type positive electrode active materials in which small and large particles with different average particle sizes are mixed are often used to increase the capacity of lithium secondary batteries. When small and large particles are mixed, the small particles with a relatively small average particle size can fill the gaps between the large particles, improving the integration density of the lithium composite oxide within a unit volume and increasing the energy density per unit volume. Summary of the Invention [Problem to be solved by the invention]

[0010] In the past, in order to alleviate the volume change of the lithium composite oxide during charging and discharging or to minimize the stress caused by the volume change and prevent damage to the particles, the degree of aggregation of the primary particles was intentionally reduced to create a certain amount of voids between the primary particles, thereby dispersing the stress caused by the volume change of the primary particles. However, such lithium composite oxides have a limitation in that they have a low energy density per unit volume.

[0011] Meanwhile, in the case of a bimodal type positive electrode active material, small particles and large particles coated with a certain material may be used in order to reduce stress applied to the small particles and large particles due to repeated charging and discharging.

[0012] In this case, when a mixture of small particles and large particles is mixed with a coating raw material and then heat-treated at the same time, the coating raw material is concentrated on the small particles having a relatively large specific surface area, which may cause a coating imbalance between the small particles and the large particles. This may cause an imbalance in particle stability between the small particles and the large particles in a bimodal type positive electrode active material, which may act as a cause of deterioration in the electrochemical properties and stability of the positive electrode active material.

[0013] In order to reduce the uneven weight distribution of the coating, it is possible to consider mixing the small particles and the large particles with the coating raw material, respectively, and then heat-treating the mixture to mix the coated small particles and the large particles. However, in this case, it is difficult to effectively fill the small particles in the large particles, and this can cause a new problem that the integration density of the lithium composite oxide in a unit volume and the energy density per unit volume cannot be sufficiently improved.

[0014] Under these circumstances, the inventors have discovered that by controlling the slope of the concentration gradient in which cobalt decreases from the surface to the center in the small particles and the large particles, respectively, it is possible to uniformly improve the particle stability of the small particles and the large particles.

[0015] Accordingly, the present invention provides a bimodal type positive electrode active material including a first lithium composite oxide which is a small particle and a second lithium composite oxide which is a large particle, the first lithium composite oxide and the second lithium composite oxide including at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide has a concentration gradient which decreases from the surface portion toward the center, thereby mitigating or preventing the occurrence of cracks, the collapse of the crystal structure, and / or the change in the crystal structure (phase transition) not only in the surface portion but also in the center portion of the first lithium composite oxide and the second lithium composite oxide, thereby improving the stability of the particles.

[0016] Another object of the present invention is to provide a bimodal type positive electrode active material comprising a first lithium composite oxide which is a small particle and a second lithium composite oxide which is a large particle, wherein the first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and the gradient of the concentration gradient of the cobalt which decreases from the surface portion to the center of the first lithium composite oxide is different from the gradient of the concentration gradient of the cobalt which decreases from the surface portion to the center of the second lithium composite oxide, thereby enabling the particle stability of the small particles and the large particles to be uniformly improved.

[0017] Another object of the present invention is to provide a positive electrode comprising the positive electrode active material defined herein.

[0018] It is yet another object of the present invention to provide a lithium secondary battery using the positive electrode defined herein. [Means for solving the problem]

[0019] According to one aspect of the present invention, there is provided a bimodal type positive electrode active material including a first lithium composite oxide in the form of small particles and a second lithium composite oxide in the form of large particles.

[0020] Here, the first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide can have a concentration gradient that decreases from the surface portion toward the center.

[0021] In this case, when the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center portion of the first lithium composite oxide is s1, and the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center portion of the second lithium composite oxide is s2, s1 and s2 can satisfy the following formula 1.

[0022] [Formula 1] s1 <s2

[0023] The first lithium composite oxide and the second lithium composite oxide are composite particles including at least one primary particle, and the primary particle is represented by Chemical Formula 1 below.

[0024] [C1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2

[0025] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, and Cu; M1 and M2 are different from each other, 0.5≦w≦1.5, 0≦x≦0.50, 0≦y≦0.20, 0≦z≦0.20.)

[0026] At least one of the first lithium composite oxide and the second lithium composite oxide may be a core-shell particle including a coating layer covering at least a part of the surface of the primary particle and the composite particle, and the coating layer may include a metal oxide represented by Chemical Formula 2 below.

[0027] [Case 2] Li a M3 b O c

[0028] (where: M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦a≦10, 0≦b≦8, 2≦c≦13, except when a and b are both 0.

[0029] According to another aspect of the present invention, there is provided a positive electrode comprising the positive electrode active material defined herein.

[0030] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the positive electrode defined herein. Effect of the Invention

[0031] The positive electrode active material according to various embodiments of the present invention is a bimodal type positive electrode active material including a first lithium composite oxide which is a small particle having a different average particle size and a second lithium composite oxide which is a large particle, and since the small particles having a relatively small average particle size can fill the gaps between the large particles, the integration density of the lithium composite oxide within a unit volume can be improved, and the energy density per unit volume can be increased.

[0032] In addition, according to the present invention, by controlling the slope of the concentration gradient in which cobalt decreases from the surface to the center in the small particles and the large particles, the particle stability of the small particles and the large particles can be uniformly improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] Hereinafter, the positive electrode active material according to the present invention and the lithium secondary battery including the positive electrode active material will be described in more detail.

[0034] positive electrode active material According to one aspect of the present invention, there is provided a bimodal type positive electrode active material including a first lithium composite oxide in the form of small particles and a second lithium composite oxide in the form of large particles.

[0035] In the present application, the range of the average particle size (D50) of small particles and large particles is not particularly limited, but in order to distinguish whether any lithium composite oxide is small particles or large particles, the following reference range of the average particle size (D50) of small particles and large particles may be determined.

[0036] The small particles refer to lithium composite oxide having an average particle size (D50) of 7 μm or less, and the large particles refer to lithium composite oxide having an average particle size (D50) of more than 7 μm. The upper limit of the average particle size (D50) of the large particles is not limited, but for example, the large particles may have an average particle size of more than 7 μm and 30.0 μm or less.

[0037] In the bimodal type positive electrode active material according to various embodiments of the present invention, the first lithium composite oxide and the second lithium composite oxide having the average particle size (D50) defined above may be present in a mixed state in a weight ratio of 5:95 to 50:50.

[0038] In this case, the first lithium composite oxide may be present in a form filled in the gaps between the second lithium composite oxides, or may be attached to the surface of the second lithium composite oxide, or may be present in a form in which the first lithium composite oxides are aggregated together. However, it is preferable that the first lithium composite oxide having a relatively small average particle size is present in a state in which it is sufficiently filled in the gaps formed by at least a plurality of the second lithium composite oxides.

[0039] When the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is excessively low, the first lithium composite oxide may not be sufficiently filled in the gaps formed by the second lithium composite oxide. On the other hand, when the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is excessively high, the ratio of the first lithium composite oxide particles agglomerated in the positive electrode active material increases, which may reduce the press density of the positive electrode active material and decrease the stability of the positive electrode active material.

[0040] The first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide can have a concentration gradient that decreases from a surface portion toward a center portion.

[0041] The first lithium composite oxide and the second lithium composite oxide are composite particles including at least one primary particle, and the primary particle is represented by Chemical Formula 1 below.

[0042] [C1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2

[0043] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, and Cu; M1 and M2 are different from each other, 0.5≦w1.5, 0≦x≦0.50, 0≦y≦0.20, 0≦z≦0.20.)

[0044] Furthermore, the first lithium composite oxide and / or the second lithium composite oxide may be a high-Ni type lithium composite oxide containing primary particles in which the concentrations (mol %) of Ni, Co, M1 and M2 in Chemical Formula 1 satisfy the following Relational Formula 1:

[0045] [Equation 1] Ni / (Ni+Co+M1+M2)≧80.0

[0046] Furthermore, the first lithium composite oxide and / or the second lithium composite oxide may be a high-Ni / low-Co type lithium composite oxide containing primary particles in which the concentrations (mol %) of Ni, Co, M1 and M2 in Chemical Formula 1 satisfy the Relational Formula 1 and the Co content is 10 mol % or less, preferably 5 mol % or less.

[0047] It is generally known that in lithium composite oxides containing at least nickel and cobalt, the structural instability of the lithium composite oxide due to Li / Ni cation mixing occurs as the Ni content increases. It has also been reported that in lithium composite oxides containing at least Ni and Co, the initial overpotential (resistance) increases as the Co content decreases, which inevitably leads to a decrease in rate characteristics.

[0048] However, the lithium composite oxide included in the positive electrode active material according to an embodiment of the present invention has a concentration gradient in which the cobalt concentration decreases from the surface portion to the center portion of the lithium composite oxide, thereby mitigating and / or preventing the structural instability and deterioration of rate characteristics of high-Ni type or high-Ni / low-Co type lithium composite oxide.

[0049] On the other hand, the lithium composite oxide contained in the positive electrode active material defined in the present application may be a secondary particle including at least one primary particle.

[0050] Here, "secondary particles containing at least one primary particle" should be interpreted as including both "particles formed by agglomeration of multiple primary particles" and "non-agglomerated particles containing a single primary particle."

[0051] The primary particles and the secondary particles may each independently be rod-shaped, elliptical and / or irregular.

[0052] When the average major axis length is used as an index showing the size of the primary particles and the secondary particles, the average major axis length of the primary particles constituting the lithium composite oxide may be 0.1 μm to 5 μm, and the average major axis length of the secondary particles may be 1 μm to 30 μm. The average major axis length of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles, and the positive electrode active material may contain particles having various average major axis lengths.

[0053] When the lithium composite oxide is "non-aggregated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles," the size (average particle size) of the primary particles contained in the "non-aggregated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles" may be larger than the primary particles (average particle size) contained in the "secondary particles formed by agglomeration of tens to hundreds or more primary particles."

[0054] Thus, lithium composite oxides which are "non-aggregated particles including a single primary particle" or "particles formed by aggregating a relatively small number of primary particles" generally require stronger heat treatment conditions (higher heat treatment temperature / longer heat treatment time) than those required for producing "secondary particles formed by aggregating tens to hundreds or more primary particles".

[0055] It is known that when heat treatment is performed at a relatively high temperature (e.g., 800°C or higher) for a long period of time, particle growth (crystal growth) is promoted, the size of individual particles increases, and a positive electrode active material with a low degree of particle aggregation is obtained.

[0056] For example, when the lithium composite oxide is "non-aggregated particles including a single primary particle" or "particles formed by aggregating a relatively small number of primary particles", the primary particles may have an average major axis length in the range of 0.5 μm to 20 μm. On the other hand, when the lithium composite oxide is "particles formed by aggregating a plurality of (tens to hundreds or more) primary particles", the primary particles may have an average major axis length in the range of 0.1 μm to 5 μm.

[0057] The primary particle may also include at least one crystallite, i.e., the primary particle may be constituted as a single crystallite, or may exist as a particle including multiple crystallites.

[0058] In one embodiment, at least one of the first lithium composite oxide and the second lithium composite oxide is a core-shell particle including a coating layer covering at least a part of the surface of the primary particle and the composite particle, and the coating layer may include a metal oxide represented by the following Chemical Formula 2.

[0059] [C2] Li a M3 b O c

[0060] (where: M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦a≦10, 0≦b≦8, 2≦c≦13, except when a and b are both 0.

[0061] The coating layer may be in a form in which different metal oxides are simultaneously present in one layer, or different metal oxides represented by Chemical Formula 2 are present in separate layers. The coating layer may also include a metal oxide containing at least Co.

[0062] The metal oxide represented by Chemical Formula 2 may be in a state of being physically and / or chemically bonded to the primary particles and / or the secondary particles. Also, the metal oxide may exist in a state of forming a solid solution with the primary particles and / or the secondary particles.

[0063] The metal oxide is an oxide of lithium and an element represented by M3 in a composite form, or an oxide of M3. The metal oxide is, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a B b O c , Li a Co b O c , Li a Al b O c , Co b O c , Al b O c , W b Oc , Zr b O c , Ti b O c Or B b O c However, the above-mentioned examples are merely given for the convenience of aiding understanding, and the metal oxide defined in the present application is not limited to the above-mentioned examples.

[0064] The metal oxide may be an oxide in which lithium and at least two elements represented by M3 are combined, or may further include a metal oxide in which lithium and at least two elements represented by M3 are combined. The metal oxide in which lithium and at least two elements represented by M3 are combined may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c It may be, but is not necessarily limited to, the above.

[0065] A concentration gradient pattern of cobalt in the first lithium composite oxide and the second lithium composite oxide included in the positive electrode active material according to the present application may be formed by the coating layer. That is, the concentration gradient of cobalt in the first lithium composite oxide and the second lithium composite oxide may be realized by the concentration of cobalt present in the primary particles and / or secondary particles and the concentration of cobalt present in the metal oxide present on the surface of the primary particles and / or secondary particles.

[0066] The concentration of the transition metal in the first lithium composite oxide and the second lithium composite oxide may be measured by various known methods. For example, the first lithium composite oxide and the second lithium composite oxide may be cross-sectionally processed, and then the concentration of the target transition metal may be analyzed by line scanning through EDS mapping. In this case, the concentration change of the target transition metal may be observed in the direction from the surface to the center of the first lithium composite oxide and the second lithium composite oxide.

[0067] In addition, the acceleration voltage (V acc ) while measuring the concentration of the target transition metal accumulated from the surface of the lithium composite oxide to a specific depth where the electron beam penetrates according to the accelerating voltage.

[0068] In the present application, the concentration of transition metals was analyzed by the above-mentioned EP-EDS method. Specifically, the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material according to the present application are each selected, and then the acceleration voltage of the electron beam irradiated to the surfaces of the selected first lithium composite oxide (small particles) and second lithium composite oxide (large particles) is changed from 1 kV to 30 kV (1 kV, 3 kV, 5 kV, 7.5 kV, 10 kV, 12.5 kV, 15 kV, 20 kV, 30 kV) to analyze the cumulative concentration (at%) of transition metals from the surfaces of the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) to a specific depth penetrated by the electron beam for each acceleration voltage.

[0069] For example, when an electron beam having an accelerating voltage of 10 kV is irradiated onto the surfaces of the first lithium composite oxide and the second lithium composite oxide to penetrate the electron beam to a depth of about 300 nm from the surfaces of the first lithium composite oxide and the second lithium composite oxide, the concentration of the target transition metal present in the region at a depth of 300 nm from the surfaces of the first lithium composite oxide and the second lithium composite oxide can be measured by the EP-EDS analysis. Also, when an electron beam having an accelerating voltage of 20 kV is irradiated onto the surfaces of the first lithium composite oxide and the second lithium composite oxide to penetrate the electron beam to a depth of about 800 nm from the surfaces of the first lithium composite oxide and the second lithium composite oxide, the concentration of the target transition metal present in the region at a depth of 800 nm from the surfaces of the first lithium composite oxide and the second lithium composite oxide can be measured by the EP-EDS analysis.

[0070] That is, when the cumulative concentration of the target transition metal measured decreases as the acceleration voltage of the electron beam irradiated to the surfaces of the first lithium composite oxide and the second lithium composite oxide increases, this can be interpreted as having a gradient in which the concentration of the target transition metal decreases from the surface portion toward the center portion of the first lithium composite oxide and the second lithium composite oxide.

[0071] When an EP-EDS (Energy Profiling-Energy Dispersive X-ray Spectroscopy) analysis is performed to measure the cumulative concentration of cobalt from the surface of the secondary particles to the depth penetrated by the electron beam using an electron beam irradiated at an accelerating voltage increasing from 1 kV to 30 kV on the surfaces of the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) included in the positive electrode active material according to the present application, the first lithium composite oxide and the second lithium composite oxide can all show a concentration gradient in which the cobalt concentration decreases from the surface to the center.

[0072] The concentration gradient in which the cobalt concentration decreases from the surface portion toward the center portion of all of the first lithium composite oxide and the second lithium composite oxide is also present when the first lithium composite oxide and the second lithium composite oxide are core-shell particles. In this case, a concentration gradient in which the cobalt concentration decreases from the shell toward the cobalt may also be present.

[0073] In this case, the cobalt concentration gradient may be a concentration gradient in which the cobalt concentration decreases continuously or discontinuously from the surface portion of the particle to the center portion. In other words, when the cobalt concentration decreases from the start point to the end point of an arbitrary section in which the cobalt concentration is measured, it can be said that the cobalt has a concentration gradient that decreases from the start point to the end point of the arbitrary section.

[0074] In this case, however, the inclinations of the cobalt concentration gradients exhibited by the first lithium composite oxide and the second lithium composite oxide may be different from each other.

[0075] In this case, when the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center portion of the first lithium composite oxide is s1 and the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center portion of the second lithium composite oxide is s2, it is preferable that s1 and s2 satisfy the following formula 1:

[0076] [Formula 1] s1 <s2

[0077] Furthermore, the slopes of the cobalt concentration gradients exhibited by the first lithium composite oxide and the second lithium composite oxide are independent of each other, but since they have the same sign, the directions of the cobalt concentration gradients are the same.

[0078] The formula 1 means that the gradient of the cobalt concentration in the second lithium composite oxide, which is a large particle, is greater than the gradient of the cobalt concentration in the first lithium composite oxide, which is a small particle.

[0079] Here, a steep concentration gradient means that the cobalt concentration decreases significantly from the surface to the center of the particle. If the first lithium composite oxide and the second lithium composite oxide have the same cobalt content, and the slope of the concentration gradient of the cobalt concentration decrease in the second lithium composite oxide is steep, it is expected that the cobalt in the second lithium composite oxide will be concentrated in the surface region relative to the cobalt in the first lithium composite oxide.

[0080] However, when the cobalt content in the second lithium composite oxide is greater than the cobalt content in the first lithium composite oxide, even if the gradient of the cobalt concentration decrease in the second lithium composite oxide is steep, the cobalt content in the core of the second lithium composite oxide may be greater than or similar to the cobalt content in the core of the first lithium composite oxide.

[0081] For example, in order to form core-shell particles, instead of coating the first lithium composite oxide and the second lithium composite oxide, respectively, when the first lithium composite oxide (or its precursor) and the second lithium composite oxide (or its precursor) are mixed with a raw material of the metal oxide represented by Chemical Formula 2 and then heat-treated, the coating raw material may be biased toward the first lithium composite oxide, which is a small particle having a relatively large specific surface area and a small density of crystal grain boundaries.

[0082] The coating layer formed on the surface of the lithium composite oxide prevents damage to particles by reducing volumetric changes of the lithium composite oxide during charging and discharging or minimizing stress caused by volumetric changes. However, if the coating raw material is concentrated in the first lithium composite oxide, the variation in particle stability between the first lithium composite oxide and the second lithium composite oxide becomes larger.

[0083] In addition, in the case of the first lithium composite oxide having a relatively small particle size and a low density of crystal grain boundaries, it is easier to form a coating layer on the inside of the secondary particles, i.e., on the surface of the primary particles, than in the case of the second lithium composite oxide. Therefore, if the coating raw material is concentrated in the first lithium composite oxide, the stability of the primary particles in the surface portion and the center portion of the second lithium composite oxide may vary.

[0084] Thus, in order to reduce or prevent the occurrence of cracks, collapse of the crystal structure, and / or change in the crystal structure (phase transition) not only in the surface portions but also in the center portions of the first lithium composite oxide and the second lithium composite oxide and to uniformly improve particle stability, it is preferable that an absolute value s1 of the slope of the cobalt concentration gradient decreasing from the surface portion to the center portion of the first lithium composite oxide and an absolute value s2 of the slope of the cobalt concentration gradient decreasing from the surface portion to the center portion of the second lithium composite oxide satisfy a predetermined relationship.

[0085] More specifically, the value s1 may be the absolute value of the slope of the cobalt concentration gradient measured in a region where the acceleration voltage of the electron beam irradiated onto the surface of the first lithium composite oxide is from 1 kV to 30 kV, and the value s2 may be the absolute value of the slope of the cobalt concentration gradient measured in a region where the acceleration voltage of the electron beam irradiated onto the surface of the second lithium composite oxide is from 1 kV to 30 kV, but is not necessarily limited thereto. The slope of the cobalt concentration gradient in the first lithium composite oxide and the second lithium composite oxide may be an absolute value measured in a predetermined region along a direction from the surface portion (shell) to the center portion (core) of the first lithium composite oxide and the second lithium composite oxide.

[0086] In one embodiment, the s1, which is an absolute value of the gradient of the cobalt concentration that decreases from the surface portion to the center portion of the first lithium composite oxide, can satisfy the following formula 2.

[0087] [Formula 2] 0.5 <s1<2.0

[0088] The absolute value of the gradient of the concentration of cobalt in the first lithium composite oxide, s1, being 0.5 or less means that there is almost no deviation in the concentration of cobalt from the surface portion to the center portion of the first lithium composite oxide. In other words, this means that the amount of cobalt in the first lithium composite oxide is insufficient. In this case, the effect of improving the stability of primary particles present in the surface portion of the first lithium composite oxide and in a region relatively adjacent to the center portion of the first lithium composite oxide may be insufficient.

[0089] On the other hand, when s1, which is the absolute value of the gradient of the concentration of cobalt in the first lithium composite oxide, is 2.0 or more, it means that the coating is concentrated on the first lithium composite oxide and the coating on the second lithium composite oxide is insufficient. In this case, the effect of improving the stability of the primary particles present in the surface portion of the second lithium composite oxide and in the region relatively adjacent to the center of the second lithium composite oxide may be insufficient.

[0090] In one embodiment, the s2, which is an absolute value of the gradient of the cobalt concentration that decreases from the surface portion to the center portion of the second lithium composite oxide, can satisfy the following formula 3.

[0091] [Formula 3] 1.5 <s2<3.0

[0092] When the absolute value of the gradient of the concentration of cobalt in the second lithium composite oxide, s2, is 1.5 or less, this means that the amount of cobalt in the second lithium composite oxide is insufficient. In this case, the effect of improving the stability of the primary particles present in the surface portion of the second lithium composite oxide and in the region relatively adjacent to the center portion of the second lithium composite oxide may be insufficient.

[0093] On the other hand, when s2, which is the absolute value of the gradient of the concentration of cobalt in the second lithium composite oxide, is 3.0 or more, it means that the coating is biased toward the second lithium composite oxide and the coating is insufficient for the first lithium composite oxide. In this case, even though the average particle size and grain boundary density are smaller than those of the second lithium composite oxide and are advantageous for coating, the absolute coating amount is insufficient, and the effect of improving the stability of the first lithium composite oxide may be insufficient.

[0094] Taking the above-mentioned formulas 1 to 3 together, cobalt in the first lithium composite oxide and the second lithium composite oxide has a concentration gradient that decreases from the surface portion toward the center, and it is preferable that the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center of the first lithium composite oxide is controlled to be smaller than the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center of the second lithium composite oxide.

[0095] Furthermore, it is preferable that the cobalt concentration measured at an acceleration voltage of 1.0 kV in EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis of the surfaces of the first lithium composite oxide and the second lithium composite oxide is higher in the second lithium composite oxide than in the first lithium composite oxide.

[0096] In this case, even if the absolute value of the gradient of the cobalt concentration decreasing from the surface portion toward the center portion of the second lithium composite oxide is larger than that of the first lithium composite oxide, a cobalt concentration that satisfies a predetermined standard can be achieved even within the center portion of the second lithium composite oxide.

[0097] For the same reason as described above, it is preferable that the cobalt concentration measured at an acceleration voltage of 30.0 kV in EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis of the surfaces of the first lithium composite oxide and the second lithium composite oxide is higher in the second lithium composite oxide than in the first lithium composite oxide.

[0098] In one embodiment, the s1 which is an absolute value of a gradient of the cobalt concentration decreasing from a surface portion toward a center portion of the first lithium composite oxide, and the s2 which is an absolute value of a gradient of the cobalt concentration decreasing from a surface portion toward a center portion of the second lithium composite oxide can satisfy the following formula 4.

[0099] [Formula 4] 1.0≦s2 / s1≦3.0

[0100] When s2 / s1 calculated by the above formula 4 is greater than 3.0, it means that the coating is excessively biased to the second lithium composite oxide compared to the first lithium composite oxide, and the coating for the first lithium composite oxide is insufficient. In this case, even though the average particle size and the density of the crystal grain boundary are smaller than those of the second lithium composite oxide, which is advantageous for coating, the absolute coating amount is insufficient, so that the effect of improving the stability of the first lithium composite oxide may be insufficient. In addition, the coating deviation between the first lithium composite oxide and the second lithium composite oxide may accelerate performance degradation due to the deviation in stability between the first lithium composite oxide and the second lithium composite oxide in a bimodal type positive electrode active material.

[0101] On the other hand, when s2 / s1 calculated by the formula 4 is less than 1.0, it means that the amount of cobalt in the second lithium composite oxide is insufficient. In this case, the effect of improving the stability of the primary particles present in the surface portion of the second lithium composite oxide and in the region relatively adjacent to the center portion of the second lithium composite oxide may be insufficient. In addition, it is preferable that s2 / s1 calculated by the formula 4 is 1.5 or more.

[0102] As described above, the first lithium composite oxide and the second lithium composite oxide may be composite particles including at least one primary particle capable of lithium intercalation / deintercalation. If the first lithium composite oxide and / or the second lithium composite oxide includes a plurality of primary particles, the plurality of primary particles may be present as secondary particles that are aggregates of each other.

[0103] The primary particle means one crystal grain or crystallite, and the secondary particle means an aggregate formed by agglomeration of a plurality of primary particles. A gap and / or a grain boundary may exist between the primary particles constituting the secondary particle.

[0104] In this case, the first lithium composite oxide and the second lithium composite oxide in the bimodal type positive electrode active material may have different degrees of aggregation of primary particles.

[0105] The degree of aggregation of primary particles in the first lithium composite oxide and the second lithium composite oxide may be measured by the density of crystal grain boundaries as defined herein.

[0106] Specifically, the density of the crystal grain boundaries may be calculated by substituting the number of crystallites placed on a virtual line crossing the center of the first lithium composite oxide and the second lithium composite oxide in a minor axis direction and the number of boundary planes between crystallites in a cross-sectional SEM image obtained by photographing cross sections of the first lithium composite oxide and the second lithium composite oxide using a scanning electron microscope (SEM) after cross-sectional processing of each of the first lithium composite oxide and the second lithium composite oxide, into the following Equation 5:

[0107] [Formula 5] Grain boundary density = (number of boundary surfaces between crystallites placed on the imaginary line / number of crystallites placed on the imaginary line)

[0108] For example, when the lithium composite oxide is a non-aggregated single particle consisting of a single crystallite, the number of crystallites placed on a virtual line crossing the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide is one. As a result, there is no boundary surface between crystallites, and the grain boundary density calculated by the formula 1 is zero.

[0109] In addition, when the lithium composite oxide is a particle formed by agglomeration of a relatively small number of primary particles, the number of crystallites (primary particles) placed on a virtual line crossing the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide is two, and therefore, there is one boundary surface between crystallites, and the grain boundary density calculated by the above formula 1 is 0.5.

[0110] Since the grain boundary density of the first lithium composite oxide, which is generally a small particle, is smaller than that of the second lithium composite oxide, it may be advantageous to coat the grain boundaries of the second lithium composite oxide in the region adjacent to the center of the first lithium composite oxide. In this case, the coating can be sufficiently performed not only on the surface portion but also on the center portion of the first lithium composite oxide with only a relatively small amount of coating raw material compared to the second lithium composite oxide.

[0111] Nevertheless, in a bimodal type positive electrode active material including the first lithium composite oxide which is a small particle and the second lithium composite oxide which is a large particle, if the proportion of the coating concentrated on the first lithium composite oxide having a relatively small average particle size and density of crystal grain boundaries can be reduced, the particle stability of the primary particles existing in a region relatively close to the center of the second lithium composite oxide can be improved.

[0112] Lithium secondary battery According to yet another aspect of the present invention, a positive electrode may be provided, the positive electrode active material layer including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. Here, the positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, since the positive electrode active material is as described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described below.

[0113] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0114] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0115] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.

[0116] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0117] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0118] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0119] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0120] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0121] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0122] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0123] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0124] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0125] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0126] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0127] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0128] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.

[0129] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0130] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskey such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0131] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and a film obtained by peeling the negative electrode slurry composition from the support may be laminated on the negative electrode current collector.

[0132] In another embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support, peeling the negative electrode slurry composition from the support, and laminating the resulting film on the negative electrode current collector.

[0133] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.

[0134] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0135] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0136] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0137] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0138] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.

[0139] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0140] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0141] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0142] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0143] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0144] Production Example 1. Production of positive electrode active material (1) Example 1 (a) The first lithium composite oxide, which is a small particle, and the NiCoAl(OH)2 hydroxide precursor, which is a large particle, of the second lithium composite oxide, were synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate. The synthesized NiCoAl(OH)2 hydroxide precursor was heated to 400°C at a rate of 2°C per minute and calcined at 400°C for 6 hours to convert it into an oxide precursor.

[0145] The oxide precursor of the first lithium composite oxide (first oxide precursor) had an average particle size (D50) of 4.0 μm, and the oxide precursor of the second lithium composite oxide (second oxide precursor) had an average particle size (D50) of 18.0 μm.

[0146] (b) The first oxide precursor and the second oxide precursor prepared in step (a) were weighed out so that the weight ratio was 20:80, and LiOH (Li / (Ni+Co+Al) molar ratio=1.05) was added and mixed, and then the mixture was heated in a sintering furnace in an O2 atmosphere at a rate of 2°C per minute up to 800°C for 12 hours to obtain an intermediate product.

[0147] (c) Distilled water was added to the intermediate product, and a 7.0 wt% aqueous cobalt sulfate solution was added so that the cobalt derived from the aqueous cobalt sulfate solution was 3.0 mol% relative to the metal elements (Ni+Co+Al) excluding lithium in the intermediate product, while stirring at 300 rpm for 1 hour, thereby coating the surfaces of the first oxide precursor and the second oxide precursor in the intermediate product with cobalt. After the reaction was completed, the intermediate product was dried at 120°C for 12 hours.

[0148] (d) The intermediate product was placed in a sintering furnace in an O2 atmosphere, the temperature was raised to 700°C at a rate of 2°C per minute, and the intermediate product was heat-treated at 700°C for 12 hours to obtain a bimodal type positive electrode active material in which the first lithium composite oxide, which is small particles, and the second lithium composite oxide, which is large particles, are mixed in a predetermined ratio.

[0149] (2) Example 2 A bimodal type positive active material was prepared in the same manner as in Example 1, except that in step (c), the cobalt sulfate aqueous solution was stirred at 400 rpm when reacting with the intermediate product.

[0150] (3) Example 3 A bimodal type positive electrode active material was prepared in the same manner as in Example 1, except that in step (c), a 5.7 wt % aqueous cobalt sulfate solution was used instead of 7.0 wt % cobalt sulfate.

[0151] (4) Example 4 A bimodal type positive electrode active material was prepared in the same manner as in Example 1, except that in step (c), the cobalt sulfate aqueous solution was added and stirred for 90 minutes instead of 1 hour.

[0152] (5) Example 5 A bimodal type positive electrode active material was prepared in the same manner as in Example 1, except that in step (b), the first oxide precursor, the second oxide precursor, LiOH (Li / (Ni+Co+Al) molar ratio=1.05) and H3BO3 (B / (Ni+Co+Al) molar ratio=0.015) were mixed and then heat-treated.

[0153] (6) Comparative Example 1 A bimodal type positive electrode active material was prepared in the same manner as in Example 1, except that in step (c), the cobalt sulfate aqueous solution was added and stirred for 30 minutes instead of 1 hour.

[0154] (7) Comparative Example 2 A bimodal type positive electrode active material was prepared in the same manner as in Example 1, except that in step (c), a 9.6 wt % aqueous cobalt sulfate solution was used instead of a 7.0 wt % aqueous cobalt sulfate solution.

[0155] (8) Reference example In step (b), the first oxide precursor, the second oxide precursor, LiOH (Li / (Ni+Co+Al) molar ratio=1.05) and H3BO3 (B / (Ni+Co+Al) molar ratio=0.015) were mixed and then heat-treated. In step (c), a bimodal type positive electrode active material was prepared in the same manner as in Example 1, except that a 9.6 wt % aqueous cobalt sulfate solution was used instead of a 7.0 wt % aqueous cobalt sulfate solution.

[0156] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 92 wt% of the positive electrode active material prepared in Preparation Example 1, 4 wt% of artificial graphite, and 4 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a 15 μm-thick aluminum film and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0157] A coin battery was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte solution containing LiPF6 at a concentration of 1.15 M in a solvent containing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7.

[0158] Experimental Example 1: EP-EDS analysis of positive electrode active material EP-EDS analysis was performed to measure the cobalt content in the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1. In the EP-EDS analysis, the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material prepared according to Preparation Example 1 were each separated, and the accelerating voltage of the electron beam irradiated to the surfaces of the separated first lithium composite oxide (small particles) and second lithium composite oxide (large particles) was changed from 1 kV to 30 kV (1 kV, 3 kV, 5 kV, 7.5 kV, 10 kV, 12.5 kV, 15 kV, 20 kV, 30 kV) to analyze the cumulative concentration (at%) of cobalt up to a specific depth penetrated by the electron beam for each accelerating voltage.

[0159] The absolute value of the slope of the cobalt concentration gradient measured in a region where the acceleration voltage of the electron beam irradiated to the surface of the first lithium composite oxide (small particles) is from 1 kV to 30 kV is defined as s1, and the absolute value of the slope of the cobalt concentration gradient measured in a region where the acceleration voltage of the electron beam irradiated to the surface of the second lithium composite oxide (large particles) is from 1 kV to 30 kV is defined as s2.

[0160] The slopes of the cobalt concentration gradient, s1 and s2, were calculated by taking the change in cobalt concentration (Δat%) on the y-axis and the change in EDS accelerating voltage (ΔkV%) on the x-axis, and were calculated as the average value obtained by adding up the slopes of each measurement region.

[0161] The EP-EDS analysis results are shown in the following Tables 1 and 2. In the following Tables 1 and 2, s1 and s2 satisfy the formulas 1 to 3 defined in the present application, but do not satisfy the formula 4 (1.0≦s2 / s1≦3.0) are shown as reference examples.

[0162] [Table 1]

[0163] [Table 2]

[0164] Referring to the results of Tables 1 and 2, it can be seen that, in the first lithium composite oxide and the second lithium composite oxide included in the bimodal positive electrode active materials according to Examples 1 to 5, a concentration gradient is formed in which the cobalt concentration decreases from the surface portion to the center, and the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion to the center of the first lithium composite oxide is smaller than the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion to the center of the second lithium composite oxide.

[0165] On the other hand, in the case of the positive electrode active materials according to Comparative Example 1 and Comparative Example 2, a concentration gradient is formed in which the cobalt concentration decreases from the surface portion toward the center, and it can be confirmed that the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center of the first lithium composite oxide is greater than the absolute value of the slope of the cobalt concentration gradient decreasing from the surface portion toward the center of the second lithium composite oxide.

[0166] (2) Cross-sectional SEM analysis of the positive electrode active material In order to measure the grain boundary density of the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material prepared in Preparation Example 1, the degree of aggregation of primary particles within secondary particles confirmed from cross-sectional SEM images was confirmed.

[0167] First, the first lithium composite oxide (small particles) and the second lithium composite oxide (large particles) contained in the positive electrode active material produced by Production Example 1 were each separated, and then cross-sectional SEM images were taken for each of the separated first lithium composite oxide (small particles) and second lithium composite oxide (large particles) using an FE-SEM (Bruker).

[0168] Next, for each of the particles observed in the cross-sectional SEM image, the number of crystallites on a virtual line crossing the center of the particle in the minor axis direction and the number of boundaries between the crystallites were substituted into the following Equation 5 to calculate the grain boundary density.

[0169] [Formula 5] Grain boundary density = (number of boundaries between primary particles placed on the imaginary line / number of primary particles placed on the imaginary line)

[0170] Table 3 below shows the average grain boundary density measured for a number of grains observed in the cross-sectional SEM image.

[0171] [Table 3]

[0172] Referring to the results in Table 3, it can be seen that the average grain boundary density of the first lithium composite oxide (small particles) in the positive electrode active material produced by Production Example 1 is smaller than the average grain boundary density of the second lithium composite oxide (large particles).

[0173] In other words, the first lithium composite oxide has a smaller grain boundary density than the second lithium composite oxide, and therefore has a relatively smaller number of primary particles inside, which means that the first lithium composite oxide also has fewer grain boundaries between primary particles than the second lithium composite oxide.

[0174] In addition, the average values ​​of the grain boundary densities of the first and second lithium composite oxides among the positive electrode active materials according to Examples 1 to 5, Comparative Example 1, Comparative Example 2, and Reference Example are almost similar, and therefore it is expected that the differences in the cumulative concentration of cobalt by accelerating voltage and the slope of the cobalt concentration gradient measured in the accelerating voltage range of 1 kV to 30 kV shown in Tables 2 and 3 are not due to the differences in the grain boundary densities shown in Table 3.

[0175] Experimental Example 2: Evaluation of the electrochemical properties of a lithium secondary battery A charge / discharge experiment was performed on the lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 using an electrochemical analyzer (Toyo, Toscat-3100) at 25° C., voltage range of 3.0 V to 4.25 V, and discharge rate of 0.2 to measure the charge and discharge capacities.

[0176] In addition, the same lithium secondary battery was charged / discharged 50 times at 25°C and 1C / 1C within a driving voltage range of 3.0V to 4.25V, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.

[0177] The measurement results are shown in Table 4 below.

[0178] [Table 4]

[0179] Referring to the results in Table 4, it can be seen that the charge / discharge efficiency and life efficiency of the lithium secondary battery using the positive electrode active material in which the absolute value of the gradient of the cobalt concentration decreasing from the surface portion to the center portion of the second lithium composite oxide is greater than the absolute value of the gradient of the cobalt concentration decreasing from the surface portion to the center portion of the first lithium composite oxide are improved.

[0180] Meanwhile, in the case of the lithium secondary battery using the positive electrode active material according to the Reference Example, the charge / discharge efficiency was measured to be almost similar to that of the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 and 2, but the life efficiency was slightly improved. However, it was confirmed that the life efficiency of the lithium secondary battery using the positive electrode active material according to the Reference Example was somewhat lower than that of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 5.

[0181] Experimental Example 3. Evaluation of the stability of positive electrode active materials and lithium secondary batteries (1) Thermal stability evaluation of positive electrode active material In order to evaluate the thermal stability of the positive electrode active material prepared in Preparation Example 1, the weight loss was measured at a heating rate of 10°C / min from 25°C to 350°C under Ar atmosphere at normal pressure using a thermogravimetric analyzer (TA Instruments, Q20). The on-set temperature at which the weight loss (thermal decomposition) peak appeared for each positive electrode active material is shown in Table 5 below.

[0182] [Table 5]

[0183] Referring to the results in Table 5, it was found that the on-set temperature at which the weight loss (thermal decomposition) peak appears in the positive electrode active materials of Examples 1 to 5 is higher than that of the positive electrode active materials of Comparative Examples 1 to 3. That is, it can be seen that the thermal stability of the positive electrode active materials of Examples 1 to 5 is superior to that of the positive electrode active materials of Comparative Examples 1 and 2.

[0184] (2) Measuring the amount of gas generated from lithium secondary batteries The lithium secondary battery prepared according to Preparation Example 2 was charged to 4.25 V at a constant current of 0.2 C, and then stored at 60° C. for 14 days to measure the volume change of the lithium secondary battery due to gas generation in the lithium secondary battery. The measurement results of the volume change are shown in Table 6 below.

[0185] [Table 6]

[0186] Referring to the results in Table 6, it can be seen that the volume change of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 5 is smaller than the volume change of the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 3.

[0187] (3) Measurement of DC-IR increase rate before and after the life of a lithium secondary battery The DC-IR of the lithium secondary battery prepared according to Preparation Example 3 after one cycle of charging under 1C condition (SOC100) and after 50 charge / discharge cycles under 1C / 1C condition were measured, and the increase in DC-IR was shown in Table 7 below.

[0188] [Table 7]

[0189] Referring to the results in Table 7, it can be seen that the resistance increase after the end of life of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 5 is smaller than the resistance increase of the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 and 2.

Claims

1. A bimodal type positive electrode active material including a first lithium composite oxide which is a small particle and a second lithium composite oxide which is a large particle, the first lithium composite oxide and the second lithium composite oxide contain at least nickel and cobalt, and the cobalt in the first lithium composite oxide and the second lithium composite oxide has a concentration gradient that decreases from a surface portion toward a center portion; When the average value of the absolute value of the gradient of the cobalt concentration that decreases from the surface portion toward the center portion of the first lithium composite oxide is denoted by s1, and the average value of the absolute value of the gradient of the cobalt concentration that decreases from the surface portion toward the center portion of the second lithium composite oxide is denoted by s2, s1 and s2 satisfy the following formula 1: The positive electrode active material, wherein s1 and s2 satisfy the following formula 4. [Formula 1] s1<s2 [Formula 4] 1.0≦s2 / s1≦3.0

2. The positive electrode active material according to claim 1 , wherein s1 satisfies the following formula 2: [Formula 2] 0.5<s1<2.0

3. The positive electrode active material according to claim 1 , wherein the s2 satisfies the following formula 3: [Formula 3] 1.5<s2<3.0

4. 2. The positive electrode active material according to claim 1, wherein, in an energy profiling-energy dispersive X-ray spectroscopy (EP-EDS) analysis in which a cumulative concentration of cobalt is measured from the surface of the first lithium composite oxide and the second lithium composite oxide to a depth penetrated by the electron beam using an electron beam irradiated at an acceleration voltage increasing from 1 kV to 30 kV to a surface of each of the first lithium composite oxide and the second lithium composite oxide, a concentration (at %) of cobalt in the second lithium composite oxide measured at an acceleration voltage of 1.0 kV is greater than a concentration (at %) of cobalt in the first lithium composite oxide.

5. 2. The positive electrode active material according to claim 1, wherein, in an Energy Profiling-Energy Dispersive X-ray Spectroscopy (EP-EDS) analysis in which a cumulative concentration of cobalt is measured from the surface of the first lithium composite oxide and the second lithium composite oxide to a depth penetrated by the electron beam using an electron beam irradiated at an acceleration voltage increasing from 1 kV to 30 kV to a surface of each of the first lithium composite oxide and the second lithium composite oxide, a concentration (at %) of cobalt in the second lithium composite oxide measured at an acceleration voltage of 30.0 kV is greater than a concentration (at %) of cobalt in the first lithium composite oxide.

6. The positive electrode active material according to claim 1 , wherein the first lithium composite oxide has an average particle size (D50) of 7 μm or less.

7. The positive electrode active material of claim 1 , wherein the second lithium composite oxide has an average particle size (D50) of more than 7 μm to 30 μm.

8. the first lithium composite oxide and the second lithium composite oxide are composite particles including at least one primary particle, The positive electrode active material according to claim 1 , wherein the primary particles are represented by the following Chemical Formula 1. [Case 1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, and Cu; M1 and M2 are different from each other, 0.5≦w≦1.5, 0≦x≦0.50, 0≦y≦0.20, 0≦z≦0.20.)

9. At least one of the first lithium composite oxide and the second lithium composite oxide is a core-shell particle including a coating layer covering at least a part of the surface of the primary particle and the composite particle, The positive electrode active material according to claim 8 , wherein the coating layer contains a metal oxide represented by the following Chemical Formula 2. [Case 2] Li a M3 b O c (where: M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦a≦10, 0≦b≦8, 2≦c≦13, except when a and b are both 0.

10. 2. The positive electrode active material according to claim 1, wherein a weight ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is 5:95 to 50:

50.

11. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 10.

12. A lithium secondary battery using the positive electrode according to claim 11.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery, positive electrode for secondary battery containing the same, and secondary battery

    JP2018536253A

  • Cathode material for secondary batteries and lithium secondary batteries containing the same

    JP2020537316A

  • Positive electrode active material for lithium secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2021509220A